Enabling superior electrochemical performances of Li10SnP2S12-based all-solid-state batteries using lithium halide electrolytes. Issue 7 (1st April 2023) - Luo, Qiyue; Yu, Chuang; Wei, Chaochao; Chen, Shuai; Chen, Shaoqing; Jiang, Ziling; Peng, Linfeng; Cheng, Shijie; Xie, Jia
Abstract: Li10 GeP2 S12 shows great potential as solid electrolytes for solid-state batteries due to its ultrahigh Li-ion conductivity. However, the high cost of Ge and the poor stability limit its applications. Replacing Ge with Sn can significantly lower the cost and maintains the high conductivity, while the corresponding Li10 SnP2 S12 still suffers the low interfacial stability with the bare high voltage layered oxide cathodes. Herein, Li10 SnP2 S12 with high Li-ion conductivity up to 4.79 mS cm −1  has been synthesized. All-solid-state battery using the cathode consisting of bare LiNi0.6 Co0.2 Mn0.2 O2 and Li10 SnP2 S12 shows low capacities and poor cyclability due to side reactions between those two particles. To improve the interfacial stability, a highly conductive Li3 InCl6 electrolyte is introduced both in the cathode mixture and between the cathode layer and Li10 SnP2 S12 solid electrolyte layer. This new configuration delivers superior electrochemical performances at different operating temperatures. It delivers high initial discharge capacities of 176.1 mAh g −1, 186.9 mAh g −1, and 73.7 mAh g −1 at 0.1C when operated at room temperature, 60 o C, and −20 o C, respectively. The superior battery performances are attributed to the excellent electrochemical stability of Li3 InCl6 electrolyte towards bare LiNi0.6 Co0.2 Mn0.2 O2 cathode. This work provides a guideline to design Li10 SnP2 S12 -based all-solid-state lithium batteries with high energy density and long span life.